On angular boundary limits of normal subharmonic functions - Berberyan, Samvel Levonovich (Eurasian Mathematical Journal, 2013)
The paper considers normal subharmonic functions defined in the unit circle. New necessary and sufficient conditions for the existence of angular limits at arbitrary points of the unit circumference are obtained. The obtained conditions are less strong than in the previous results of different authors. Examples confirming the significance of these conditions are given.